Industrial Energy Efficiency Towards Green Deal Transition. Case of Latvia. - Locmelis Kristaps (Sciendo, 2021)
Energy efficiency policy has been one of the European Union top priorities for decades and will continue to play a vital role in the next 10 years with the introduction of The Clean energy for all Europeans. Likewise, in Latvia energy efficiency has been given high priority; however, the energy efficiency targets for industry has lacked ambitions. This research focuses on evaluating the Latvian industrial energy efficiency policy using top-down approach and benchmarking energy intensity of Latvian industry to the average of the European Union’s. Results confirm that on average Latvian industry consumes 2.6 times more energy to produce the same amount of value added compared to the average in the European Union; however, every saved energy unit in Latvia would save twice less CO2 emissions considering already largely decarbonized energy mix. In the spotlights of the Green Deal proposed by the European Commission, much higher contribution in terms of CO2 reduction and energy efficiency will be expected from the industry. Nevertheless, energy efficiency targets for Latvian industry should be sector-specific, separately addressing CO2 intensive sectors, and non-intensive CO2 sectors with low added value.